Sensitivitas Harga Bahan Pangan Pokok Jelang Idul Fitri Tahun 2023 Di Pasar Baruga Kota Kendari - Dedy Alfatha; Samsul Alam Fyka (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
Determining relatively high prices will cause consumers to move to other producers, or look for new products that have better product quality. This shows that determining price sensitivity must be appropriate. The aim of the research is to determine the price sensitivity of staple foods ahead of Eid al-Fitr in 2023 at Pasar Baruga, Kendari city. Determination of the research area was carried out purposively based on the consideration that Baruga Market is one of the central distributors of staple foods. The sampling technique uses the Slovin formula. The number of respondents who were staple food traders was 44 people. Data analysis uses qualitative descriptive. The results of the research show that: The price sensitivity of staple foods ahead of Eid al-Fitr in 2023 at Baruga Market, Kendari City, means that on average there has been an increase in both the number of goods offered and the price level. For head rice the average selling price difference is Rp. 5,125, for broiler meat the average selling price difference is Rp. 8,750, purebred chicken eggs with an average selling price difference of Rp. the average difference in selling price is IDR 2,786, Sedaap cooking oil with an average difference in selling price is IDR 2,429, Shallots with an average difference in selling price is IDR 15,286 and the average difference in the number of goods sold is 10 Kg .